Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1978
DOI: 10.1042/bj1700093
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between vitamin D-stimulated calcium transport and intestinal calcium-binding protein in the chicken

Abstract: 1. The rapid stimulation of intestinal Ca(2+) transport observed in vitamin D-deficient chicks after receiving 1,25-dihydroxycholecalciferol has necessitated a re-evaluation of the correlation hitherto observed between this stimulation and the induction of calcium-binding protein synthesis. By 1h after a dose of 125ng of 1,25-dihydroxycholecalciferol, Ca(2+) transport is increased. This is at least 2h before calcium-binding protein can be detected immunologically and 1h before synthesis of the protein begins o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…The protein synthesis theory of 1,25(OH)2D3 function has been questioned recently (9,10,12) (10,13,14). However, this lack oftemporal correspondence has never been observed in this laboratory when truly vitamin Ddeficient chicks were used (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein synthesis theory of 1,25(OH)2D3 function has been questioned recently (9,10,12) (10,13,14). However, this lack oftemporal correspondence has never been observed in this laboratory when truly vitamin Ddeficient chicks were used (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The primary effect of D3 was considered to be a modification of membrane phospholipids and thereby an increase in the permeability of the brush border membrane to Ca2+, with subsequent steps in the absorption ofcalcium somewhat secondary to this event (11,12). In this vein, Spencer et al (13), Bikle et al (10), and Thomasset et aL (14) reported that the administration of a single dose of 1,25(OH)2D3 to vitamin D-deficient animals stimulates calcium absorption prior to the induction of the synthesis of calciumbinding protein (CaBP), a protein product ofthe genomic action of the 1,25(OH)2D3. However, this lack of temporal correlation between CaBP synthesis and 1,25(OH)2D3-stimulated calcium absorption is contrary to our experience, as documented in this report.…”
mentioning
confidence: 99%
“…Previous studies using an in vitro translation assay [36] showed that mRNA coding for 28-kDa cholecalcin appears in the chick intestine 2 h after a single calcitriol dose administered to vitamin-Ddeficient birds. The relatively low yield of 28-kDa cholecalcin in the cell-free system compared with that of the 9-kDa protein [14,37] may account for the difference between the short delay for 9-kDa-cholecalcin mRNA stimulation and the later 28-kDa-cholecalcin mRNA induction. However, the changes in the concentrations of both 9-kDa cholecalcin and its mRNA were dissociated in the period immediately following hormonal induction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ornithine decarboxylase (EC 4.1.1.17), spermidine N ' -acetyltransferase (EC 2.3.1.57), polyamine oxidase (EC 1.4.3.6). transport activity apparently preceded the synthesis of calbindin [20,25,261. The role of calbindin in the intestinal calcium transport mechanism is still a matter of controversy.…”
mentioning
confidence: 99%